Optimizing Small Business Management through Collaborative Training and Education in Business Applications - Ana Sopanah; Zahir Rusyad; Zulkarnain Zulkarnain (Trescode Green Organization, 2023)
The purpose of this activity is to empower MSMEs and prospective MSMEs in the Malang City, Malang Regency and Batu City areas with knowledge and skills in digital marketing, so that they can increase the visibility, sales and growth of their business in the rapidly growing digital era. . The methods used in this digital marketing workshop include in-depth presentations by experienced facilitators, interactive discussions to share experiences and understanding, as well as practical exercises to apply concepts in real situations. Apart from that, there are also case analysis sessions, self-studies, and participants' active involvement in solving digital marketing challenges relevant to their business. The result of this digital marketing workshop activity is an increase in participants' understanding and skills in digital marketing, which allows them to design and implement more effective marketing strategies online. Participants are also able to recognize new opportunities in the digital business world and have the ability to optimize the use of digital tools to increase the visibility, engagement and sales of their business.